(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
The study was conducted on a group of German cockroach adults and nymphs، and it was divided into groups، the first group included 40 male insects and females distributed into 4 groups equally، and the second group included the nymphs stage with the same number as the previous number and the same groups. The results showed as follows: at a concentration of 5000 ppm، the nymphs died after 4 days، at a rate of 20%، and when exposed to a dose of boric acid، all members of the sample died after 11 days، As for adult adults، 40% of their members died within the first 3 days، and all adults died after a period of a days. In comparison between the two tests، it is noted through statistical analysis that there are no significant differences P=0.05.